2018
DOI: 10.2118/191145-pa
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response of Reservoir and Well Completion of the First Offshore Methane-Hydrate Production Test at the Eastern Nankai Trough: A Coupled Thermo-Hydromechanical Analysis

Abstract: Summary During gas production from offshore gas-HBS, there are concerns regarding the settlement of the seabed and the possibility that frictional stress will develop along the production casing. This frictional stress is caused by a change in the effective stress induced by water movement caused by depressurization and dissociation of hydrate as well as gas generation and thermal changes, all of which are interconnected. The authors have developed a multiphase-coupled simulator by use of a fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The OCR values of the overburden layer are derived from triaxial test data on formation core samples retrieved at the Nankai Trough [34], whereas OCR = 1 is employed for the reservoir and underburden layers, in which case Equation 1 reduces to Jaky's formula. This means that the reservoir and underburden layers are normally consolidated, and this is consistent with the triaxial compression test results on reservoir and underburden sediment cores recovered at the Nankai Trough [9].…”
Section: Simulation Steps 221 Initial Conditionssupporting
confidence: 86%
See 2 more Smart Citations
“…The OCR values of the overburden layer are derived from triaxial test data on formation core samples retrieved at the Nankai Trough [34], whereas OCR = 1 is employed for the reservoir and underburden layers, in which case Equation 1 reduces to Jaky's formula. This means that the reservoir and underburden layers are normally consolidated, and this is consistent with the triaxial compression test results on reservoir and underburden sediment cores recovered at the Nankai Trough [9].…”
Section: Simulation Steps 221 Initial Conditionssupporting
confidence: 86%
“…However, if gas production longer than 20 days were simulated, greater reservoir compaction would occur, and there is a risk of well failure. Yoneda et al [9] also simulated gas production at the Nankai Trough and found that tensile deformation of the well developed in the overburden layer due to reservoir compaction, which might cause the tensile failure of the gravel pack to induce sand production. This highlights the importance of analyzing the tensile deformation of the well during reservoir compaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the test was terminated prematurely due to sand production (Uchida, Klar and Yamamoto, 2016). One of the potential causes of sand production is considered to be well failure induced by the compaction of the unconsolidated methane hydrate reservoir (Yoneda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differences between fully coupled and semi-coupled models were analyzed. Yoneda et al [10] developed a coupled thermo-hydro-mechanical (THM) simulator to evaluate the mechanical stability of a hydrate-bearing reservoir and well completion at the eastern Nankai Trough. The results showed that the mechanical deformation occurred in a much wider area than the range of hydrate dissociation and large shear stress occurred near the production well.…”
Section: Introductionmentioning
confidence: 99%